Knowledge, attitude, and practices of adolescent school girls regarding menstrual hygiene in Lucknow district - Ruby Khatoon; Shahzeb Ansari; Syed Abid Asghar; Beena Sachan; Zeashan H Zaidi; Sharique Ahmad (Asian Journal of Medical Sciences, 2023)
Background: Girls’ adolescence has been recognized as a unique period that occurs as they cross the threshold from childhood to adulthood. Menstruation is typically viewed in Indian society as unclean. A negative attitude about this condition has been perpetuated by efforts to isolate and restrict menstruation females in the household. Numerous investigations have discovered restrictions in daily activities. On the other hand, maintaining good cleanliness habits during menstruation is important for reproductive health since it reduces vulnerability to infections of the reproductive tract. Aims and Objectives: The aim of the study was to assess knowledge and attitude about menstrual health among adolescent girls in rural and urban schools in Lucknow district and to find out practices of menstrual hygiene among them. Materials and Methods: The study unit consists of 410 teenage school-going females who live in both urban and rural regions of the Lucknow district. There was a multi-stage random sampling. A pre-developed and pre-tested interview schedule was employed to obtain data. Participants were questioned about their personal cleanliness, which need to be covered in the academic program. Results: Four hundred and ten adolescent girls who were enrolled in school participated in the study. The majority of girls in this survey (52.8%) are between the ages of 17 and 19. 87.6% of the girls reported being ignorant of menstruation before menarche. While 41.6% of the girls were unaware of the organ from which bleeding originates, around 68.2% of the girls believed that the primary reason of menstruation is physiological and unrelated to any sickness. At the age of 10–13 years, 42.60% of the girls reached menarche. The majority of participants (60.80%) gave accurate responses to the question about the typical menstrual cycle’s average length. Only 35.27% of the girls were aware of the proper menarche age. Of them, 65.50% were aware of the issues with their reproductive health. Conclusion: Lack of education among mothers and other female family members may contribute to girls’ lack of knowledge and awareness of menstruation. Misinformation, pre-conceptions, limitations, and a lack of knowledge around menstruation come in many different forms. As a result, when the entire family is familiar with the phenomena of menstruation, age-old prohibitions, conventional preconceptions, incorrect ideas, and negative attitudes may be successfully erased.